2020
DOI: 10.1016/j.cities.2019.102476
|View full text |Cite
|
Sign up to set email alerts
|

Community participation in cultural heritage management: A systematic literature review comparing Chinese and international practices

Abstract: Community participation is an essential issue in heritage management. The international heritage organisation ICCROM published a guidance document discussing people-centred approaches to heritage management in 2015. Cultural heritage management is recommended to be carried out through a community participation process. Despite the growing literature on community participation in cultural heritage management, little research has been done on comparing Chinese to international approaches. Although in China sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 71 publications
1
41
0
1
Order By: Relevance
“…Similarly, the different thematic emphasis revealed by this research could be explained by the change in discourse in domains such as heritage and sustainable urban development [90,94]. For example, factors referring to civic engagement present increased discussion and articulation probably due to the rising interest in participatory practices in heritage management [95]. Additionally, a growing interest in the practicing of adaptive reuse might have triggered measures and spread coping strategies that made both design and technical aspects and legal requirements less regarded as challenges.…”
Section: Factorsmentioning
confidence: 89%
“…Similarly, the different thematic emphasis revealed by this research could be explained by the change in discourse in domains such as heritage and sustainable urban development [90,94]. For example, factors referring to civic engagement present increased discussion and articulation probably due to the rising interest in participatory practices in heritage management [95]. Additionally, a growing interest in the practicing of adaptive reuse might have triggered measures and spread coping strategies that made both design and technical aspects and legal requirements less regarded as challenges.…”
Section: Factorsmentioning
confidence: 89%
“…In that sense, the smart city concept often promotes community participation in decision making and the development of a participatory approach as support to urban governance [75]. Current architectural heritage management practice shows the importance of community involvement and shifts from a centralized governing process to a more holistic approach that meets the preferences of the residents [76,77]. The architectural indicators include the possibilities for the protection and restoration of existing architectural heritage facilities.…”
Section: Theoretical Background 21 Architectural Heritage In Smart mentioning
confidence: 99%
“…Villagers have a strong demand for local resources to develop tourism, but they hope someone can plan and design it in depth. Although Liufang village has not been developed for tourism, these demands of residents are in line with the bottomup community participation of traditional village's tourism development [40]. Liufang village is very suitable for such a tourism development model.…”
Section: Discussionmentioning
confidence: 99%
“…Liufang village is very suitable for such a tourism development model. It is suggested that the development of tourism should be carried out gradually from tourism training measures, community tourism organization, participation rules and regulations, etc., especially with respect to economic policy, it is suggested a set of community participation bonus system be established that derives from community autonomy participation in tourism from bottom to top [40,41].…”
Section: Discussionmentioning
confidence: 99%